IMPROVE - Innovative Modelling Approaches for Production Systems to Raise Validatable Efficiency Intelligent Methods for the Factory of the Future - Niggemann, Oliver; Schüller, Peter (Technologien für die intelligente Automation, 2018)
This open access work presents selected results from the European research and innovation project IMPROVE which yielded novel data-based solutions to enhance machine reliability and efficiency in the fields of simulation and optimization, condition monitoring, alarm management, and quality prediction.